2003
DOI: 10.1016/s0008-6363(02)00656-9
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Na+ regulation in cardiac myocytes

Abstract: Intracellular [Na+] ([Na+]i) is regulated in cardiac myocytes by a balance of Na+ influx and efflux mechanisms. In the normal cell there is a large steady state electrochemical gradient favoring Na+ influx. This potential energy is used by numerous transport mechanisms, including Na+ channels and transporters which couple Na+ influx to either co- or counter-transport of other ions and solutes. Six sarcolemmal Na+ influx pathways are discussed in relatively quantitative terms: Na+ channels, Na+/Ca2+ exchange, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
229
0
10

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(245 citation statements)
references
References 129 publications
6
229
0
10
Order By: Relevance
“…The a4 isoform is not capable of directly transporting H C (Blanco et al 1999). Instead, and as has been shown for somatic cells (Bers et al 2003, Despa et al 2004, the Na,K-ATPase can functionally couple to the Na C /H C exchanger (NHE) to regulate pH in sperm. In this manner, the a4 isoform provides spermatozoa with an inwardly directed Na C gradient that provides the electrochemical energy to drive the secondary movement of protons out of the cells.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The a4 isoform is not capable of directly transporting H C (Blanco et al 1999). Instead, and as has been shown for somatic cells (Bers et al 2003, Despa et al 2004, the Na,K-ATPase can functionally couple to the Na C /H C exchanger (NHE) to regulate pH in sperm. In this manner, the a4 isoform provides spermatozoa with an inwardly directed Na C gradient that provides the electrochemical energy to drive the secondary movement of protons out of the cells.…”
Section: Discussionmentioning
confidence: 95%
“…An important mechanism that controls proton concentration in somatic cells operates utilizing the transmembrane Na C gradient generated by the Na,K-ATPase. In this manner, the Na,K-ATPase indirectly controls pH in the cells (Bers et al 2003, Despa et al 2004. We explored whether the Na,K-ATPase plays a similar role in spermatozoa.…”
Section: Function Of A4 Is Important For Sperm Membrane Potentialmentioning
confidence: 99%
“…23,24) Furthermore, Royer, et al reported that aging Scn5a-knockout mice (Scn5a +/-) show progressive impairment of atrial and ventricular conduction associated with myocardial rearrangements and fibrosis, 25) and Papadatos, et al reported a reduction of approximately 50% in sodium conductance in Scn5a +/-mice as well as several defects including impaired atrioventricular conduction, delayed intramyocardial conduction, increased ventricular refractoriness, and ventricular tachycardia with characteristics of reentrant excitation. 26) Martin, et al also demonstrated that the electrocardiographic features in an Scn5a mouse establish it as a suitable model for Brugada syndrome and demonstrate abnormal conduction and repolarization phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…The disequilibrium in ion transport makes the Na pump electrogenic. The Na + gradient created by the Na,K-ATPase is coupled to a multitude of secondary active transporters which mediate the uptake of amino acids, glucose, HCO 3 -, and neurotransmitters [1], as well as the extrusion of Ca ++ and H + [2]. Moreover, the maintenance of the Na + and K + gradients, in combination with selective ion channels, gives rise to resting membrane potential in most animal cells [for review see 3,4].…”
Section: Introductionmentioning
confidence: 99%